Realising «Fortress Europe»: «Managing» migrants and refugees at the borders of Greece - Voutira, Eftihia (The Greek Review of Social Research, 2013)
This paper considers the emergence of a migration regime in the making at the South-eastern borders of Europe with special reference to Greece and the role of FRONTEX as the new European border guard often acting in lieu of the state. Using a bio-political approach, we consider practices of human rights violations at the Greek reception centres in Evros and identify the actors involved in policing the borders. The key question is that of accountability: who guards the guards guarding Europe’s borders?